Economic Viability Analysis of Super Seeder Machine Adoption in Wheat Cultivation: A Case Study in Haryana: ECONOMIC ANALYSIS OF SUPER SEEDER MACHINE IN WHEAT - Bishnoi, Raveena; Vijay Kumar,; D.K. Bishnoi,; M.S. Meena, (Annals of Arid Zone, 2024)
There is a need to investigate the potential for conserving essential inputs through resource-conserving alternative technologies in agriculture, such as the super seeder technique and happy seeder, etc. The study focusses the economic viability of the super seeder machine used in wheat farming in Haryana. The blocks, villages, and respondents were chosen using a multi-stage random selection procedure. The study was conducted in the Karnal and Kaithal districts of Haryana in 2021-2022. Using conventional and super seeder paddy straw management techniques, a sample of 100 wheat growing farmers was chosen. The viability of the machinery was assessed using the payback period and break-even point. The payback period was 2.08 years for wheat crop planting using the super seeder. The machine’s net present value and benefit-cost ratio were assessed as Rs. 18718.03 and 1.52, respectively. The machine’s break-even points and break even hours were 50.01 ha and 81.50 hrs., respectively.